Extensive T‐Wave Inversion Associated With Chest Pain: Elucidating the Underlying Truth - Jing‐Xiu Li; Xin‐Xin Di; Min Gao; Xue‐Qi Li (Annals of Noninvasive Electrocardiology)
ABSTRACT A patient with episodic chest pain, diaphoresis, amaurosis, and dizziness, along with a history of hypertension, presented with electrocardiographic findings of ST elevation in aVR, diffuse T‐wave inversion, and QTc prolongation. Initial diagnosis of NSTEMI was reconsidered after coronary angiography excluded significant stenosis, revealing myocardial bridging. Echocardiography and cardiac MRI showed preserved function without ischemia. Markedly elevated plasma renin and urinary normetanephrine, along with a retroperitoneal mass, suggested paraganglioma. Laparoscopic resection confirmed a 4.0 × 3.5 cm paraganglioma. This case highlights the importance of recognizing atypical ECG patterns that may mimic ischemia in catecholamine‐secreting tumors to guide timely diagnosis and intervention.